2015
DOI: 10.1130/b31201.1
|View full text |Cite
|
Sign up to set email alerts
|

Mineral reactions associated with hydrocarbon paleomigration in the Huincul High, Neuquén Basin, Argentina

Abstract: Bleaching of red beds by the migration of reducing pore fluids is a widespread phenomenon, with most previous work on the topic focused on detailed studies in the southwestern United States, and to a lesser extent Germany. Herein, we report on widespread bleaching of Cretaceous red beds in the Neuquén Basin and the relationship of this bleaching to hydrocarbon migration. In the Cerro Granito area of the Huincul High, Neuquén Basin, the basal deposits of the Neuquén Group (Candeleros and Huincul Formations) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Tubes and clusters of concretions formed by poikilotopic calcite2 with red luminescence are similar to calcite pipes described in the Candeleros and Huincul Formations at El Porvenir area (Rainoldi et al, 2015) and in other reservoir rocks associated with faults (e.g., Entrada Sandstone, Utah; Garden et al, 2001). These concretions indicate a change in partial pressure of CH 4 and/or CO 2 rather than signaling fluid mixing.…”
Section: Authigenic Minerals Formed During Early Diagenesissupporting
confidence: 57%
See 1 more Smart Citation
“…Tubes and clusters of concretions formed by poikilotopic calcite2 with red luminescence are similar to calcite pipes described in the Candeleros and Huincul Formations at El Porvenir area (Rainoldi et al, 2015) and in other reservoir rocks associated with faults (e.g., Entrada Sandstone, Utah; Garden et al, 2001). These concretions indicate a change in partial pressure of CH 4 and/or CO 2 rather than signaling fluid mixing.…”
Section: Authigenic Minerals Formed During Early Diagenesissupporting
confidence: 57%
“…During the Andean orogeny, reactivations of previous Triassic and Jurassic structures at the Huincul High (Maretto and Pángaro, 2005) triggered subsurface fluid seepage (formation water + hydrocarbons), breaking seals (Vaca Muerta Formation), and producing the up-flow of oil and formation water from the Lotena, Mulichinco, and Centenario reservoir rocks (Cabaleiro et al, 2002;Montagna et al, 2010) to the Neuquén Group. Evidence of this process is the conspicuous bitumen impregnations in the most permeable strata of the Neuquén Group described in the study area, in the Los Chihuidos High (e.g., Sapo Sur and Grillo Cu deposits, Rainoldi et al, 2014), and in other regions of the Huincul High (e.g., Barda González, La Cuprosa, and El Porvenir SHC deposits; Giusiano et al, 2006Giusiano et al, , 2008Pons et al, 2009;Paz et al, 2014;Rainoldi et al, 2015). Additional evidence for oil emplacement in the Huincul Formation at Tordillos is found in the numerous organic-rich fluid inclusions hosted in the micro-quartz overgrowths, calcite3, 4, and barite2 cements (see also Pons et al, 2015a).…”
Section: Alteration Of Redbeds By Liquid Hydrocarbonsmentioning
confidence: 88%
“…The organic matter in Taunsa uranium ore is possibly related with dead oil (solidified HC). This observation is supported by the extensive bleaching visible in the host sandstone on the outcrop which is generally considered an effect of petroleum migration into oxidized rocks (Schumacher and Abrams., 1996;Petrovic et al, 2008;Rainoldi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the research of geomorphic characteristics and mineral compositions mostly adopts qualitative or semi quantitative methods, and there are many such studies. For example, Rainoldi et al (2015) identified red beds by studying the color of geomorphic characteristics and hematite in mineral compositions, and studied the mechanism of red beds bleaching. Uchida et al (2000) distinguished red sandstone, yellowish brown sandstone, and green sandstone according to the content https://doi.org/10.5194/egusphere-2023-2590 Preprint.…”
Section: Introductionmentioning
confidence: 99%